The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
Proceedings of the 18th Conference on Computational Linguistics - 2000
DOI: 10.3115/990820.990864
|View full text |Cite
|
Sign up to set email alerts
|

Effects of adjective orientation and gradability on sentence subjectivity

Abstract: Subjectivity is a pragmatic, sentence-level feature that has important implications for texl processing applicalions such as information exlractiou and information iclricwd. We study tile elfeels of dymunic adjectives, semantically oriented adjectives, and gradable ad.ieclivcs on a simple subjectivity classiiicr, and establish lhat lhcy arc strong predictors of subjectivity. A novel trainable mclhod thai statistically combines two indicators of gradability is presented and ewlhlalcd, complementing exisling aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
243
0
7

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 452 publications
(255 citation statements)
references
References 15 publications
(20 reference statements)
1
243
0
7
Order By: Relevance
“…Previous work on unsupervised sentiment classification has shown that adjectives and adverbs are good indicators of sentiment (Hatzivassiloglou, 1997(Hatzivassiloglou, , 2000, [19], Turney 2002 [5]). It has also been shown that adjectives present around a given topic are indicative of sentiment related to the particular topic [11], [20].…”
Section: ) Default Classifiermentioning
confidence: 99%
“…Previous work on unsupervised sentiment classification has shown that adjectives and adverbs are good indicators of sentiment (Hatzivassiloglou, 1997(Hatzivassiloglou, , 2000, [19], Turney 2002 [5]). It has also been shown that adjectives present around a given topic are indicative of sentiment related to the particular topic [11], [20].…”
Section: ) Default Classifiermentioning
confidence: 99%
“…For sentiment classification of each identified subjective sentence, it used a similar method to the method in [95], but with many more seed words (rather than only two used in [95]), and the score function was log-likelihood ratio. The same problem is studied in [35] considering gradable adjectives. In [28], a semi-supervised learning method is applied, and in [46], the decision is made by simply summing up opinion words in a sentence.…”
Section: Assumption Of Sentence-level Sentiment Classificationmentioning
confidence: 99%
“…For example, sentences (1), (2), (6) and (8) do not express any opinions. The issue of subjectivity has been extensively studied in the literature [34,35,79,80,97,99,100,102,103,104].…”
Section: Objective Of Mining Direct Opinionsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, some Unsupervised Learning techniques have been very successful as well, as it is unsupervised technique based on the PMI-IR algorithm that is used to estimate the semantic orientation of a phrase by measuring the similarity of pairs of words or phrases [60]. Alternative methods have been proposed, like the Bootstrapping Method for Building Subjectivity Lexicons for Languages with Scarce Resources [6], the techniques for generating a quality lexicon [59], the recognition of contextual polarity in [69] and the gradability of subjective sentences based on adjective orientation [26]. In all these cases, the focus of the research is at the sentence/phrase level.…”
Section: Through 2014mentioning
confidence: 99%